Change Management in an Era of Uncertainty: The Role of Strategic and Adaptive Leadership (A Case Study of the Local Government of Jombang Regency) - Mutawakkil Alallah (Lembaga Institute Development of Social Economic Cociety, 2025)
This article examines strategic and adaptive leadership in the context of change management in the Jombang Regency Government, particularly in an era of uncertainty. Using literature reviews and interviews, this study found that adaptive leadership is crucial for addressing challenges arising from social, economic, and environmental change. The results indicate that implementing flexible and responsive leadership strategies can enhance the effectiveness of change management in local.